Pricing as a Strategic Capability - Shantanu Dutta; Mark Bergen; Daniel Levy; Mark Ritson; Mark Zbaracki (MIT Sloan Management Review, 2002)
Companies that know how to set the right prices for their products and services understand that pricing isn't simply a matter of good tactics. By investing in specific areas of organizational capital, they've made it a strategic weapon that competitors can only envy.
Keywords: M10; M21; M31; L23; L26; E31; L11; 330; Pricing; Strategy; Human Capital; Social Capital; Marketing; Systems Technology